Neanderthal last stand? Thoughts on Iberian refugia in late MIS 3. (11th October 2020) - Straus, Lawrence Guy
ABSTRACT: The history of the idea of Neanderthal/Mousterian refugia on the Iberian Peninsula over the past three decades is reviewed. Despite the recent re‐datings of several key sites that have cast doubt on late survivals, it continues to seem to be the case that Aurignacian ( sensu lato ) industries appeared relatively early in northern Spain, but not in southern Spain or Portugal. Although arguments for extremely late survival in Gibraltar are questioned, new information from sites in Murcia and a more conservative reading of the Gorham's Cave record seem to support the thesis of late Middle Paleolithic survival and late early Upper Paleolithic arrival in the south. Major problems continue to be the lack of either Neanderthal or Cro‐Magnon human remains of late Middle Paleolithic or early Upper Paleolithic age in Iberia and the ambiguity of the Châtelperronian record in northern Spain.